Fictions of Eichmann: the authentic self, authenticity, and the facts of atrocity. Issue 7 (9th August 2019) - Donig, Deb
ABSTRACT: This essay chronicles a turning point in the concept of legal evidence as it is used to establish the reality of atrocity. In the wake of the Eichmann trial that began in 1961 and Hannah Arendt's coverage of the trial in her landmark thesis, Eichmann in Jerusalem: A Report on the Banality of Evil, the discourse of 'authenticity' became central to representing atrocity, as atrocity became enfolded within legal discourse, rendered in terms of legal concepts of truth and verification. Yet the concept of 'authenticity' itself became contested, torn between the demands of aesthetic representation on the one hand and legal representation on the other. Using current research on Eichmann alongside my archival investigation into Arendt and Eichmann's papers, I juxtapose Arendt's version of the 'real' Eichmann, drafted during the Jerusalem trial in 1961, with Kurt Vonnegut Jr.'s character, Walter Campbell Jr., who bears an uncanny resemblance to Eichmann in his 1961 Mother Night . Doubling the historical figure of Eichmann, Mother Night oscillates between fictional and factual discourse in its attempt to locate an authentic representation of atrocity. I argue that in the attempt to determine and assess the facts of atrocity, fiction may itself produce a type of authentic factuality.